The lowest detected stellar Fe abundance: the halo star SMSS J160540.18−144323.1. (17th July 2019) - Nordlander, T; Bessell, M S; Da Costa, G S; Mackey, A D; Asplund, M; Casey, A R; Chiti, A; Ezzeddine, R; Frebel, A; Lind, K; Marino, A F; Murphy, S J; et al.
ABSTRACT: We report the discovery of SMSS J160540.18−144323.1, a new ultra metal-poor halo star discovered with the SkyMapper telescope. We measure [Fe/H]= -6.2 ± 0.2 (1D LTE), the lowest ever detected abundance of iron in a star. The star is strongly carbon-enhanced, [C/Fe] = 3.9 ± 0.2, while other abundances are compatible with an α-enhanced solar-like pattern with [Ca/Fe] = 0.4 ± 0.2, [Mg/Fe] = 0.6 ± 0.2, [Ti/Fe] = 0.8 ± 0.2, and no significant s- or r-process enrichment, [Sr/Fe] 0.2 and [Ba/Fe] 1.0 (3σ limits). Population III stars exploding as fallback supernovae may explain both the strong carbon enhancement and the apparent lack of enhancement of odd- Z and neutron-capture element abundances. Grids of supernova models computed for metal-free progenitor stars yield good matches for stars of about 10 M_ imparting a low kinetic energy on the supernova ejecta, while models for stars more massive than roughly 20 M_ are incompatible with the observed abundance pattern.